Analytical and clinical validation of a novel MeltPlus TB-NTM/RIF platform for simultaneous detection of Mycobacterium tuberculosis complex, Non-Tuberculous Mycobacteria and rifampicin resistance - Wang, Zhuo; Zou, Yuanwu; Wei, Zihan; Bai, Guanghong; Wang, Xiaolin; Qu, Shaoyi; Shi, Jie; Jiang, Yaping; Gu, Cuijiao (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundRapid and accurate diagnosis of tuberculosis, particularly rifampin (RIF)-resistant tuberculosis (RR-TB) and Non-Tuberculous Mycobacteria (NTM), is essential for implementing appropriate proper therapy to benefit patients and improve TB/NTM patient management.MethodsIn this study, we developed a novel MeltPlus MTB-NTM/RIF platform, designed to simultaneously detect Mycobacterium tuberculosis complex (MTBC), NTM and RIF resistance. The platform was evaluated for its limit of detection (LOD) and specificity before clinical validation, followed by a prospective single-center study in patients with presumptive TB cases.ResultsThe calculated LOD for MTBC, NTM and RIF susceptibility was found to be 10.31 CFU/mL, 57.55 CFU/mL and 48.584 CFU/mL, respectively. The assay showed a sensitivity of 98.76% (95% CI: 96.41-99.74%) and a specificity of 94.42% (95% CI: 90.82-96.92%) for MTBC detection compared to the bacteriological TB standard. For NTM detection, the assay demonstrated a sensitivity of 91.98% (95% CI: 76.32-98.14%) and a specificity of 99.59% (95% CI: 98.54-99.95%). RIF resistance detection showed a sensitivity of 90.24% (95% CI:76.87-97.28%) and specificity of 95.98% (95% CI: 91.89-98.37%), with a high level of diagnostic agreement (Kappa: 0.8338) compared to GeneXpert. Sanger sequencing revealed that novel assay correctly classifies 98.6% of study cases as RIF resistant or susceptible, slightly higher that of GeneXpert.DiscussionThese findings indicate that the novel MeltPlus MTB-NTM/RIF platform provides a rapid and accurate method for the simultaneously detecting MTBC, NTM, and RIF resistance, making it a promising tool for clinical TB/NTM diagnosis and management, further multi-center and field studies are recommended to validate its broader applicability.